Proprietățile celulelor stem spermatogoniale în mediul nișelor fiziologice și metabolice testiculare - Balan, Ion; Gavojdian, Dinu; Budevici, Alexandr; Roșca, Nicolae; Buzan, Vladimir; Balacci, Sergiu; Osipciuc, Galina; Furdui, Vlada; Harea, Vasile; Cretu, Roman; Bacu, Gheorghe; Țurcanu, Parascovia; et al. (Editura USM, 2024)
Spermatogenesis is a continuous process, maintained by the self-renewal and differentiation of spermatogonial stem cells (SSC), which arise from undifferentiated precursors (gonocytes) in the physiological conditions of the testicular cell niche. SSC serve as the foundation for the physiology of continuous spermatogenesis, they have the ability to self-renew by differentiation to produce spermatozoa suitable for fertilization, therefore the knowledge of the regulatory processes of SSC is of great importance for understanding the fundamental molecular mechanisms of the function of these cells in spermatogenesis. By strict physiological regulation, spermatogonial transitions occur with a complete non-exploitation of equivalent changes in metabolism, a conserved overregulation of mitochondrial function, biogenesis and oxidative phosphorylation in spermatogony differentiation, as well as the relationship between metabolism and the external microenvironment. In the present paper we have tried to review the current state of research in CSS physiology and biology, as well as their molecular regulation, in the physiological and metabolic niches, necessary for fundamental investigations and possible practical applications. Elucidation of the exact mechanisms and characteristics of testicular maturation events and gonocyte transition to SSC by activation of CSS-specific pathways or early embryonic establishment of transcriptional profiling of neonatal and prepubertal spermatogonia will contribute to new achievements of biological, physiological and metabolic aspects of SSC. Increased knowledge regarding the biology, physiology and metabolism of SSC will improve our understanding of the possibilities of applying SSC tools and manipulations in the evolution of spermatogenesis mechanisms.
Keywords: Spermatogonial stem cells; spermatogenesis; microenvironment